Stimulating Children's Moral and Religious Development: Analysis of the Use of Puzzle Learning Media - Rohmadanis Rohmadanis; Heldanita Heldanita; Yulia Novita; Nurkamelia Mukhtar AH; Nurhayati Nurhayati; Zuhairansyah Arifin; Siti bt Samaun (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2025)
This research is motivated by the low religious values of early childhood at Azalia School Pekanbaru. The purpose of this study was to determine the process of improving religious values in early childhood using puzzle media. This study was a classroom action esearch, with the subjects being the teacher and 12 students. The object of this study was the Pillar of Islam media. This research was conducted in two cycles, each with two meetings. Data collection techniques used were observation, tests, interviews, and documentation. The data analysis technique used was qualitative descriptive analysis with percentages. Based on the results of the research and data analysis, it was shown that the implementation of the Pillar of Islam media can improve the religious values of early childhood at Azalia School Pekanbaru. This can be seen from the fact that before the corrective action, students' reading comprehension skills only reached the category of not yet developed. After the action was implemented in the first cycle, the average score of students increased to the category of beginning to develop  and in the second cycle, it increased to the category of developing as expected. Thus, it can be concluded that the implementation of the Pillar of Islam media can improve the religious values of early childhood at Azalia School Pekanbaru. Keywords: Puzzle Media, Values, Religion, Early AgeAbstrak: Penelitian ini di latarbelakangi oleh rendahnya nilai-nilai agama anak usia dini di RA Azalia Pekanbaru. Tujuan penelitian ini ialah untuk mengetahui proses peningkatan nilai-nilai agama anak usia dini dengan menggunakan media puzzle. Penelitian ini merupakan penelitian tindakan kelas, subjek dalam penelitian ini adalah guru dan 12 peserta didik. Objek dalam penelitian ini adalah media pillar of islam. Penelitian ini dilakukan dalam 2 siklus, setiap siklus 2 kali pertemuan. Teknik pengumpulan data menggunakan observasi, tes, wawancara dan dokumentasi. Sedangkan teknik analisis data yang digunakan yaitu analisis dekskriptif kualitatif dengan persentase. Berdasarkan hasil penelitian dan analisis data menunjukkan bahwa penerapan media pillar of islam dapat meningkatkan nilai-nilai agama anak usia dini di RA Azalia Pekanbaru. Hal ini dapat diketahui sebelum tindakan perbaikan, keterampilan membaca pemahaman siswa hanya mencapai kategori belum berkembang (BB). Setelah dilakukan tindakan pada siklus I nilai rata-rata anak didik meningkat dengan kategori mulai berkembang (MB) dan pada siklus II meningkat kategori berkembang sesuai harapan (BSH). Dengan demikian dapat disimpulkan bahwa penerapan media pillar of islam dapat meningkatkan nilai-nilai agama anak usia dini di RA Azalia Pekanbaru.Kata Kunci: Media Puzzle, Nilai-Nilai, Agama, Usia Dini